2014
DOI: 10.1093/ejo/cju008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the length of the mandibular ramus and the condylar process: a comparison of OPG, CBCT, CT, MRI, and lateral cephalometric measurements

Abstract: All 3D imaging procedures yielded nearly equal results when used to measure the CondProc and RH. MRI is recommended because it avoids ionizing radiation and has higher sensitivity in the detection of inflammation. A 2-year threshold for detecting growth in the follow-up period should be taken into account for all 3D imaging methods. Measuring the RH is recommended for the follow-up of condylar growth because reference values for annual increments are published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 53 publications
5
29
0
1
Order By: Relevance
“…Considering that studies comparing conventional computed tomography (CT) or cone-beam computed tomography (CBCT) to LCR showed very similar differences in lateral cephalometric measurements [21, 27, 28] and that CT-techniques are geometrically accurate under normal conditions [29], it is legitimate to compare these results to ours. The hypothesis that intrinsic limitations of LCR were the main error source in the present study is strongly supported by ex vivo studies, which showed very high concordance between measurements on MRI and CT [30] or MRI and CBCT [31] [32]. …”
Section: Discussionsupporting
confidence: 72%
“…Considering that studies comparing conventional computed tomography (CT) or cone-beam computed tomography (CBCT) to LCR showed very similar differences in lateral cephalometric measurements [21, 27, 28] and that CT-techniques are geometrically accurate under normal conditions [29], it is legitimate to compare these results to ours. The hypothesis that intrinsic limitations of LCR were the main error source in the present study is strongly supported by ex vivo studies, which showed very high concordance between measurements on MRI and CT [30] or MRI and CBCT [31] [32]. …”
Section: Discussionsupporting
confidence: 72%
“…The observed accuracies (in terms of mean, distribution and range of the average differences) are similar to the results portrayed in various other investigations for linear measurements performed with isosurface (Periago et al, 2008), direct volume rendering (Fernandes et al, 2014), MPR (Sun et al, 2011, Patcas et al, 2012, Patel et al, 2014 and maximum intensity projection (Markic et al, 2015), all demonstrating insufficient sub-millimetre accuracy for sub-millimetre voxel data.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 86%
“…Moreover, these studies have used magnetic resonance imaging and laser scans to measure facial morphology. 27,28 The present study, to our knowledge, is the first to report a relationship between GHR gene variants and threedimensional mandibular morphology using CBCT imaging, which accurately measures not only soft tissues but also bone morphology, 29 and is therefore useful for examining the complex structure of the mandible.…”
Section: Discussionmentioning
confidence: 71%